Performance of Hevea clones from IAC 300 series selected in the northwestern region of São Paulo State, Brazil - Gonçalves, Paulo de Souza; Bortoletto, Nelson; Furtado, Edson Luiz; Sambugaro, Rosana; Bataglia, Ondino Cleante (Pesquisa Agropecuaria Brasileira, 2001)
The present paper shows the performance of 19 rubber tree [Hevea brasiliensis (Willd. ex Adr. de Juss.) Muell. Arg.] originated from Hevea breeding programme conducted at the Instituto Agronômico de Campinas (IAC) and evaluated in a small scale trial in the northwestern of São Paulo State, Brazil. The old popular clone RRIM 600 of Malaysian origin was used as control. The trial was laid out in a randomized block design with three replications. Concerned to yielding the clone IAC 40 recorded highest yield (62.22 g/tree/tap) over three years of tapping which was followed by IAC 301 (57.67 g/tree/tap) and IAC 300 (50.61 g/tree/tap) yielding 154%, 138% and 123% superior to the control clone and RRIM 600 whereas recorded 41.04 tree/tap. All selected clones were of vigorous growing, with the girth at opening ranging from 37.81 cm for IAC 317 to 50.90 cm for IAC 315 and tappability ranging from 20.0% for IAC 317 to 100% for IAC 315. All the clones experienced low to very low incidence of wind damage. All selected clones showed low to very low incidence of dry trees. Fifteen clones showed high resistance and five presented moderate resistance to anthrachnose panel canker disease similarly to RRIM 600.